Study on boulders of megalith 3 at the Wietrzychowice site (Central Poland) - Pawlikowski, Maciej; Jaranowski, Maciej; Papiernik, Piotr (Acta Geographica Lodziensia, 2020)
Boulders from Wietrzychowice megaliths underwent geological, mineralogical and petrographic study. Pink and grey granitoids were more numerous than other types of erratic stones. Boulders used in building the stone walls of the megalith’s construction had been processed by means of “flaking” technique, rock-cutting technology, mixed “flaking” and rock-cutting technologies, and by drilling. Initial research has revealed the presence of Cretaceous and Jurassic flint stones in glaciofluvial gravel in the vicinity of the site. They underwent preliminary technological, mineralogical and geochemical analysis. The research was conducted by means of modern mineralogical methods, including polarised and scanning microscopy and atomic absorption spectroscopy.